FORMANT PARAMETERS FOR TONGUE POSITION IN /R/ TRILL DYSARTHRIA THERAPY - Putri, Dewa Ayu Dyah Pertiwi; Subagia, I Ketut; Aryaningsih, Ni Rai Ayu Putri; Devi, Ni Kadek Dwi Permata (Universitas Islam Sumatera Utara (UISU), 2024)
This research aims to further research in determining the formant parameters for tongue position in pronouncing phoneme /r/ trill correctly for people with dysarthria. Observation method was used in collecting data in the form of consonant and vowel sounds from 4 dysarthria samples and 4 non-dysarthria samples. The data were analyzed by using equivalent intralingual method. The result showed that dysarthria samples were found to have tongue position lower and more back compared to non-dysarthria samples. This condition caused difficulty for the tip of the tongue of dysarthria samples to reach the alveolar—the place of which the phoneme /r/ trill is produced. Based on the condition, formant range needed as parameter for people with dysarthria to estimate whether they have placed their tip of the tongue correctly during the therapy. Further, the range of formants proposed was F1 (height of tongue) at an average of 480 Hz and F2-F1 (backness of tongue) at an average of 1.651 Hz.